Predatory activity and molecular signature of a new Indian isolate of Duddingtonia flagrans for use in biological control of caprine parasitic gastroenteritis - SANYAL, P K; MUKHOPADHYAYA, PRATAP N (The Indian Journal of Animal Sciences, 2014)
A new isolate (DF-S2550) of Duddingtonia, flagrans, a naturally occurring nematophagous fungus. was screened for its suitability of using them as biocontrol agents against nematode parasites of ruminants using growth assay. predatory activity. germination potential and ability t6 survive ruminant gut passage. An attempt was also made to get its molecular signature through randomly amplified polymorphic DNA fingerprint. The data were compared with those ora previously screcncd isolate of D.flagralls (DF-S2507). The effect offceding chlamydosporcs of the isolate to goats naturally infected with trichostrongyles. upon the translation of pre-parasitic stages from faecal pellets to the surrounding herbage was also studied to substantiate possible biological control. The study indicated that the isolate (DF-S2550) was better in terms of growth, predatory activity, production and germination of chlamydospores, compared to the previously screened isolate (DF-S2507). A consistent multiple arbitrary amplicon profile generated from the total DNA was unique for each of the isolates. The inoculated fungus could be recovered from faeces of fungus fed goats aild could significantly prevent translation of infective larvae to the surrounding herbage. A significant effect (P<0.05) of the fungus on the larval populations was also observed in in vitro faecal cultures from day 8 of feeding ofchlamydospores onwards. The new isolate proved to be a promising biocontrol candidate lor use against nematode parasites of ruminants.